Comparing social media use, discussion, political trust and political engagement among university students in China and Hong Kong: an application of the O–S–R–O–R model. Issue 1 (2nd January 2017) - Li, Xueqing; Chan, Michael
ABSTRACT: Adopting the Orientation–Stimuli–Reasoning–Orientation–Response (O–S–R–O–R) model of political communication effects, this study examines the mediating roles of online/offline political discussion and political trust on the relationship between social media information seeking and online/offline political participation in China and Hong Kong. Findings through structural equation modeling showed that the relationship between information seeking and online participation was mediated by online discussion for both samples. Moreover, the relationship between information seeking and offline participation was mediated by offline discussion, and offline discussion mediated the relationship between information seeking and online participation. Political trust did not mediate any of the relationships in China and Hong Kong and all significant paths involving political trust were negative. Implications of the findings for youth political participation in China and Hong Kong are discussed.